FAKTOR–FAKTOR YANG MEMPENGARUHI KEMAUAN UNTUK MEMBAYAR PAJAK DENGAN KESADARAN MEMBAYAR PAJAK SEBAGAI VARIABEL INTERVENING (Studi Kasus Wajib Pajak Orang Pribadi Yang Melakukan Pekerjaan Bebas Yang Terdaftar Di KPP Pratama Semarang Tengah Satu) - Rahman Adi Nugroho; Zulaikha Zulaikha (Diponegoro Journal of Accounting, 2012)
This research aimed to find factors that affect taxpayers willingness to pay taxes, case study on individual taxpayers who perform as a freelancer that registered at KPP Pratama Semarang Tengah Satu. As these factors are the realizaliton of tax paying knowledge and understanding of taxation laws, and a good perception of the effectiveness of the tax system. Data was collected by using a random sampling toward 80 respondents from questionnaire distribution. After the data was collected, the data was analyzed by using the SPSS program to test whether the model used in this study quite appropriate as the model analyzed. Then the regression analysis was used to test the relationship between the variables above. The results of this research indicated that knowledge and understanding of taxation law, service quality, and a good perception of the effectiveness of the taxation system had a significant effect toward willingness to pay taxes. Also awareness to pay taxes had a significant effect toward willingness to pay taxes.